The Artinskian Siderópolis Member macroflora, Rio Bonito Formation and its stratigraphical correlation with other early Permian macrofloras of Paraná Basin, Brazil - Mary Elizabeth Cerruti Bernardes-de-Oliveira; Sandra Eiko Mune; Maria Judite Garcia; Roberto Iannuzzi; Margot Guerra-Sommer; André Jasper; Pauline Sabina Kavali; Mahesh Shivanna; Karoline Gonçalves Pereira (Geologia USP. Série Científica, 2016)
An overview of the composition of the paleoflora preserved in clay-siltstones of the Siderópolis Member, Rio Bonito Formation is presented in order to establish phytostratigraphical comparisons with other Late Pennsylvanian and Cisuralian paleofloras of the Paraná Basin. The Rio Bonito Formation, the most important of the coal bearing lithostratigraphic units of the Paraná Basin belongs to the Gondwana I Supersequence (Pennsylvanian-Early Triassic). The Siderópolis paleoflora occurs in the uppermost layers of coal of Rio Bonito Formation in Santa Catarina coalfield in four distinct localities of the State of Santa Catarina: Lauro Muller, Criciúma, São Marcos and Treviso. In this paleoflora the glossopterid leaves predominate with an evident dominance of the genus Glossopteris over Gangamopteris, followed by Cordaitalean leaves (Noeggerathiopsis) and seeds (Cordaicarpus, Samaropsis, Cornucarpus). Sterile fronds are common and few are fertile (Sphenopteris, Pecopteris, Ponsotheca and Notoangaridium). Pteridosperm reproductive structures (Arberia, Arberiopsis, Ottokaria) are not frequent and branches of conifers (Brasilocladus, Buriadia) are rare. Concerning other paleofloras of the basin, the Siderópolis paleoflora is distinguished by high diversity and many exclusive taxa showing only few similarities with some paleofloras registered in Rio Grande do Sul, occurring in outcrops of the Rio Bonito Formation such as Morro do Papaléo (upper section) and Quitéria. The differences may reflect an upper stratigraphic position, but may also indicate differences in sedimentation and / or in paleoecological conditions.